Heart rate variability following youth concussion: how do autonomic regulation and concussion symptoms differ over time postinjury?. Issue 1 (1st October 2018) - Paniccia, Melissa; Verweel, Lee; Thomas, Scott G; Taha, Tim; Keightley, Michelle; Wilson, Katherine E; Reed, Nick
Abstract : Objectives: Following youth concussion, objective physiological indicators are needed to corroborate changes in subjective clinical measures. The objectives of the current study were to: (1) explore the effect of concussion on heart rate variability (HRV) across days postinjury in youth athletes aged 13–18 years old, compared with healthy age-matched and sex-matched controls and (2) examine the relationship between postconcussion symptom domains (physical, cognitive, fatigue and emotional) and HRV. Methods: Prospective, longitudinal, case-control study (N=44). This study comprised 29 concussed athletes between the ages of 13 and 18 years old (21 females, 8 males) and 15 age-matched and sex-matched controls). All participants completed baseline testing, which included demographic information (age, sex, concussion history), self-reported concussion symptoms (Post-Concussion Symptom Inventory [PCSI]) and a 24-hour heart rate recording via the Polar RS800CX system. The PCSI and HRV were collected weekly while the participant was symptomatic and then 1, 3 and 6 months following symptom resolution. HRV variables included time and frequency domain measures. Data visualisations and mixed effects modelling were used to derive parsimonious models. Results: HRV increased across days postinjury. Concussion symptom domains (physical, cognitive, fatigue and emotional) all had a significant main effect on HRV; concussed participants who reported more symptoms had higher HRV compared with those who reported fewer symptoms. Visualisations of HRV depict the recovery trajectory as non-linear across time. No significant differences on HRV measures were found between concussed and control participants. Conclusion: These preliminary findings provide the foundation to understand the varied trajectory and relationship between objective physiological measures and subjective symptom reporting.